2020
DOI: 10.3390/ijerph17082714
|View full text |Cite
|
Sign up to set email alerts
|

How Perceived Quality of Care and Job Satisfaction Are Associated with Intention to Leave the Profession in Young Nurses and Physicians

Abstract: German hospitals are now confronted with major challenges from both shortages and fluctuations in the numbers of physicians and nurses. This makes it even more important that physicians and nurses do not prematurely leave patient care. The objective of the present study was to improve our understanding of the factors that trigger intentions to leave the profession. For this purpose, data from 1060 young physicians and nurses in hospital care were analysed. Intentions to leave the profession was assessed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 42 publications
2
43
0
1
Order By: Relevance
“…The pandemic caused vast closures and travel bans in the global attempt to control it, which has had economic and psychological impacts on the public. In addition, it imposed an unprecedented demand on healthcare systems and workers worldwide [ 14 ]. Studies have reported that COVID-19 has impacted healthcare workers physically and psychologically, many of whom reported fears of contracting the disease or infecting a loved one [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic caused vast closures and travel bans in the global attempt to control it, which has had economic and psychological impacts on the public. In addition, it imposed an unprecedented demand on healthcare systems and workers worldwide [ 14 ]. Studies have reported that COVID-19 has impacted healthcare workers physically and psychologically, many of whom reported fears of contracting the disease or infecting a loved one [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare is associated with relevant risks not only for patients, but also for healthcare professionals [1]. Besides well-known risks to physical integrity like needle stick injuries [2] or psychological stress [1,3,4], unanticipated clinical events or outcomes (often caused by mistakes in healthcare) do not only harm patients. They also traumatise healthcare professionals, who may thus become so-called second victims [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, X (work-related fatigue) was also added to the model from step 3, and the effect of M (job satisfaction) was retained. Suppose the effect of X is retained when the effect of M in the model will be assumed as partial mediation [34]. Hayes described that this kind of analysis was performed using PROCESS.…”
Section: Discussionmentioning
confidence: 99%